Amplifying Management Research For The Common Good: Lessons For Curious Individuals And Organizations - Charles Malka, Shalom (International Journal of Psychosocial Rehabilitation, 2023)
Research papers appear almost exclusively in academic journals and/or in sponsored journals of professional associations. Access to those papers is typically blocked unless you are a paid member of one of these organizations. Consider for instance, the publications of the Academy of Management and those of the International Association of Applied Business Research. Each one of these organizations has five journals that can only be accessed by their paid members. Similarly, the American Psychological Association with its 89 different journals operates from the same premise. Put differently, the possibility of non-members gaining access to published management research in any of those journals is very slim. So, the reader may ask, what practical value do such papers have for audiences outside academia? Keeping a lid on scientific knowledge does very little for the common good. Common sense suggests that to be of value to society at large, scientific journals should be open and available to any interested party, whether an organization or an individual, regardless of their membership status. This has yet to happen. A more recent development involves the trend to turn management of scientific journals, once university-based, to publishing houses. You may be granted access to an article of interest but it would cost you a fee. Nothing is free. This of course further limits dissemination of knowledge to non-members and non-paid audiences. Of particular interest to us is how management research can promote a more applicable and transparent knowledge for the benefit of the public good? This very question shapes the principles that guide movements such as the Responsible Research in Business and Management movement. This question is also central to initiatives taken by the Principles for Responsible Management Educations, and is aligned with the more recent writings of leading scholars (e.g., Kitchener & Delbridge, 2020; Wickert, Post, Doh, Prescott & Principe, 2021). Similarly, and more recently, the American Psychological Association’s January 2023 Monitor on Psychology highlighted the field’s desire to communicate the psychology science to a wider audience.